Elevated Cholesterol as Biographical Work – Expanding the Concept of ‘Biographical Disruption’ - Felde, Lina Hoel (Qualitative Sociology Review, 2011)
The concept of ‘biographical disruption’ has been a leading framework for studies of the experience of chronic illness. A symptomless chronic condition – bereft of bodily signs ‒ does not similarly present biographical disruption. People with elevated cholesterol are healthy at the same time as medical regimens signal sickness. The empirical material presented in this article, based on interviews with people with elevated cholesterol, suggests that a more appropriate metaphor could be ‘biographical work’ in such instances. The aim of this article is to discuss how people with the symptomless condition of elevated cholesterol continually construct elevated cholesterol in everyday life doing biographical work along shifting contexts. The vocabulary of biographical work constructs a subject who is continually working on building situationally-appropriate identities embedded in the shifting contexts of being sick or not sick. The article shows how people ongoingly ‘do’ elevated cholesterol, creating a mother-cholesterol-identity, a guest-cholesterol-identity et cetera, navigating the dilemma of absence of bodily signs (signaling healthiness) and medical regimens (indicating sickness) against shifting rhythms of biographical particulars in everyday life. Linkages of medical regimens with the rhythms of mothering, vacationing, being a guest et cetera create contexts – ever-emerging ‘cholesterol-biographical rhythms’ ‒ for accomplishing and stretching the cholesterol identity from situation to situation, being adequately compliant with medical regimens.